Continuous aerosol size separator using inertial microfluidics and its application to airborne bacteria and viruses - Hong, Seung Chan; Kang, Joon Sang; Lee, Jung Eun; Kim, Sang Soo; Jung, Jae Hee (Royal Society of Chemistry, 2015)
A microchannel-based aerosol size separator that separates submicron aerosols according to particle inertial differences and Dean vortices in the airflow was developed for use in low-cost, portable, real-time aerosol collectors, detectors, concentrators and other such devices. The microfluidic inertial separator was furthermore applied to simultaneously separate airborne microorganisms by size, such as airborne viruses and bacteria from larger aerosols and viral particles from bacterial cells. The entire system was designed by numerical simulation and analysis. In addition, its performance was evaluated experimentally using airborne standard polystyrene latex (PSL) particles. In addition, two airborne microorganisms, Adenovirus 40 and Staphylococcus epidermidis, were used to verify the performance of the separator. The separation ratios of each bioaerosol were measured using real-time aerosol measurement instruments and quantitative polymerase chain reaction (qPCR) analysis. The system was composed of two 90 degrees curved microchannels and three outlets for separating the virus, bacteria and larger particles. About 70% of 3 mu m particles but almost none of the bioaerosols were separated out at the first outlet. In addition, more than 70% of S. epidermidis and similar to 70% Adenovirus were separated out at the second and third outlets, respectively. Unwanted particle loss in the system was less than 10%. The results indicated not only good separation of bioaerosols but also the potential of our separator for use in bioaerosol applications.
Keywords: BIOAEROSOL COLLECTION; QUANTITATIVE PCR; TIME; EFFICIENCY; INFLUENZA; DISEASE